Using family history and health risk behaviors to determine predictors of depressive symptoms in Central American immigrant mothers. (5th December 2012) - Maradiegue, Ann H.; Lyon, Debra E.; Meyers, Melanie F.
Abstract: In this study, depressive symptomatology in Central American immigrant mothers with adolescent daughters living in the USA was explored. Using the Center for Epidemiologic Studies Depression Short Scale, the Family History Scale, an Acculturation Scale, and the core section of the Youth Conduct Disorder scale from the National Health and Nutrition Examination Survey, 101 Central American mothers were analyzed to identify predictors of depressive symptoms. Over one‐third of the participants had depressive symptoms. There were no significant findings for acculturation as a predictor of depressive symptoms. Predictors that related to depressive symptomatology were a positive family history of depression, marital status (divorced), and having a daughter engaged in health risk behaviors. Clinicians working with mothers from Central America should consider risk of depression, whether there is a family history of depression; and additional stresses, such as the health risk behaviors of adolescents. Unprecedented levels of immigration around the world underscore the importance of meeting the healthcare needs of culturally‐diverse groups.